Brome mosaic virus detected in Kansas wheat co-infected with other common wheat viruses - Ranabhat, Nar B.; Fellers, John P.; Bruce, Myron A.; Rupp, Jessica L. Shoup (Frontiers in Plant Science, 2023)
Wheat breeders are developing new virus-resistant varieties; however, it is assumed that only a few viruses or well-known viruses are present in the field. New sequencing technology is allowing for better determination of natural field virus populations. For three years, 2019-2021, Kansas wheat field surveys were conducted to determine the constituents of natural field virus populations using nanopore sequencing. During analysis, brome mosaic virus (BMV) was identified for the first time in Kansas but was in association with other wheat viruses. Brome mosaic virus was identified from 29 out of 47 different Kansas counties sampled and 44% of the total samples. BMV was found co-infected with wheat streak mosaic virus (WSMV) and Triticum mosaic virus (TriMV) in 27.8% of the samples, with WSMV only (13.9%) and co-infected with WSMV + TriMV + High Plains wheat mosaic emaravirus (HPWMoV) (13.9%). RNA genomes of Kansas BMV isolates had 99.4 to 100% nucleotide and amino acid sequence identity, respectively, to each other. RNA2a possessed relatively high divergence (π = 0.01) compared to RNA1a and RNA3a (π = 0.004). Coding regions of all BMV RNAs were considered negative for purifying selection pressure as nonsynonymous and synonymous nucleotide ratio was less than one (dNs/dS >1). The identification of BMV in Kansas virus populations adds another layer of complexity to plant breeding. This work provides information to improve tools to aid in monitoring, detecting, and determining the variation within BMV.